Baicalein inhibits cell growth and increases cisplatin sensitivity of A549 and H460 cells via miR‐424‐3p and targeting PTEN/PI3K/Akt pathway - Lu, Chunya (J Cell Mol Med, 2018)
Lung cancer is the leading cause of death in individuals with malignant disease. Non‐small‐cell lung cancer (NSCLC) is the most common type of lung cancer, and chemotherapy drugs such as cisplatin are the most widely used treatment for this disease. Baicalein is a purified flavonoid compound that has been reported to inhibit cancer cell growth and metastasis and increase sensitization to chemotherapeutic drugs via different pathways. Therefore, we assessed the effects of baicalein on the proliferation, apoptosis and cisplatin sensitivity in the NSCLC A549 and H460 cell lines and determined the pathways through which baicalein exerts its effects. Baicalein was slightly toxic to normal human bronchial NHBE cells but inhibited growth, induced apoptosis and increased cisplatin sensitivity in A549 and H460 cells. Baicalein down‐regulated miR‐424‐3p, up‐regulated PTEN expression and down‐regulated expression of PI3K and p‐Akt in A549 and H460 cells. Dual‐luciferase reporter assay demonstrated that PTEN is a target gene of miR‐424‐3p, and overexpression of miR‐424‐3p or silencing of PTEN partially attenuated the effects of baicalein on A549 and H460 cells. Taken together, we concluded that baicalein inhibits cell growth and increases cisplatin sensitivity to A549 and H460 cells via down‐regulation of miR‐424‐3p and targeting the PTEN/PI3K/Akt pathway.